2022
DOI: 10.1186/s40035-022-00280-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of motor symptom improvement by long-term Tai Chi training in Parkinson’s disease patients

Abstract: Background Tai Chi has been shown to improve motor symptoms in Parkinson’s disease (PD), but its long-term effects and the related mechanisms remain to be elucidated. In this study, we investigated the effects of long-term Tai Chi training on motor symptoms in PD and the underlying mechanisms. Methods Ninety-five early-stage PD patients were enrolled and randomly divided into Tai Chi (n = 32), brisk walking (n = 31) and no-exercise (n = 32) groups.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 45 publications
(42 reference statements)
1
62
0
Order By: Relevance
“…Table 1 lists the characteristics of each of the included studies, which were published between 2006 and 2022. Seven studies were conducted in China (Gao et al, 2014;Zhang et al, 2015;Liu et al, 2016;Wan et al, 2021;Li et al, 2022), four in the USA (Hackney and Earhart, 2008;Li et al, 2012;Amano et al, 2013;Vergara-Diaz et al, 2018), two in Korea (Choi et al, 2013;Lee et al, 2018), one in Germany (Schmitz-Hübsch et al, 2006), and one in Turkey (Kurt et al, 2018). The TCE program was used to treat PD in all experimental groups, with nine studies using Tai Chi and six studies using Qigong.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 lists the characteristics of each of the included studies, which were published between 2006 and 2022. Seven studies were conducted in China (Gao et al, 2014;Zhang et al, 2015;Liu et al, 2016;Wan et al, 2021;Li et al, 2022), four in the USA (Hackney and Earhart, 2008;Li et al, 2012;Amano et al, 2013;Vergara-Diaz et al, 2018), two in Korea (Choi et al, 2013;Lee et al, 2018), one in Germany (Schmitz-Hübsch et al, 2006), and one in Turkey (Kurt et al, 2018). The TCE program was used to treat PD in all experimental groups, with nine studies using Tai Chi and six studies using Qigong.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The quality of the studies ranged between fair and good (score range: 5-9 points), with 80% of studies being classified as good quality and 12% as fair quality. Nine studies used a concealed allocation procedure (Schmitz-Hübsch et al, 2006;Li et al, 2012Li et al, , 2022Gao et al, 2014;Zhang et al, 2015;Kurt et al, 2018;Lee et al, 2018;Vergara-Diaz et al, 2018;Wan et al, 2021), and all reported random assignment. We could not blind patients and therapists because this was an interventional movement study.…”
Section: Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Another detrimental neurodegenerative disorder, Parkinson’s disease (PD), also exhibits higher peripheral concentrations of inflammatory markers—including IL-6, TNF, IL-1β, IL-2, IL-10, CRP and regulated upon activation, normal T cell expressed and presumably secreted (RANTES)—according to a meta-analysis that included 25 studies [ 80 ]. In an RCT with early-stage PD patients, tai chi practice significantly reduced IL-1β, IL-7, IL-9 compared to usual care; however, the effects were equivalent to brisk walking [ 59 ]. For MBI studies with PD patients reporting inflammatory outcomes, there was only one study; therefore, more RCTs are expected to discuss the effects of MBI on inflammation in PD conditions.…”
Section: Potential Effects Of Mbi On the Immune Systemmentioning
confidence: 99%